Cost-effectiveness analysis of orbital atherectomy plus balloon angioplasty vs balloon angioplasty alone in subjects with calcified femoropopliteal lesions - Weinstock B; Dattilo R; Diage T (Dove Medical Press, 2014)
Barry Weinstock,1 Raymond Dattilo,2 Tiffini Diage3 1Orlando Health Heart Institute, Mid-Florida Cardiology Specialists, Orlando, FL, USA; 2Department of Cardiology, St Francis Health Center, Topeka, KS, USA; 3North American Science Association (NAMSA), Sunnyvale, CA, USA Introduction: As cost considerations become increasingly critical when selecting optimal endovascular treatment strategies, a cost-benefit analysis was conducted comparing the Diamondback 360°® Orbital Atherectomy System (OAS) (Cardiovascular Systems, Inc., St Paul, MN, USA) and balloon angioplasty (BA) vs BA alone for treatment of calcified femoropopliteal lesions. Patients and methods: The clinical outcomes from COMPLIANCE 360°, a prospective, multicenter, randomized study comparing OAS+BA vs BA alone for treatment of calcified femoropopliteal lesions, were correlated with cost data and previously published quality of life data. Site of service, hospital charges, and associated medical resource utilization were obtained from Uniform Billing statements for index treatments and associated revascularizations out to 1 year. Hospital costs were estimated using hospital-specific, procedure-specific cost-to-charge ratios. Length of stay and procedural data were collected from participating study sites. Results: Twenty-five subjects with 38 lesions and 25 subjects with 27 lesions were randomized to the OAS+BA and BA-alone groups, respectively. Mean hospital charges (US$51,755 vs US$39,922) and estimated hospital costs (US$15,100 vs US$11,016) were higher for OAS+BA compared with BA alone (not statistically significant). Stent utilization was statistically significantly higher with BA-alone treatment for all subjects (1.1 vs 0.1, P=0.001) and in the subset of subjects with one lesion (1.0 vs 0.1, P<0.00001). There was a significant difference in cost for single-lesion versus multiple-lesion treatment. Using costs and quality-adjusted life years (QALYs) for the single-lesion cohort, the 1-year incremental cost of OAS+BA vs BA alone was US$549, and incremental QALY was 0.16. This results in an incremental cost-effectiveness ratio of US$3,441, well below the US$50,000 threshold. Conclusion: One-year index procedure cost and cost-effectiveness were comparable for OAS+BA vs BA alone. This study provides compelling cost-effectiveness data for using atherectomy for treatment of calcified femoropopliteal lesions, a longstanding challenge for peripheral artery disease interventionalists. Keywords: peripheral vascular disease, orbital atherectomy, cost analysis